Oral language skills and mental health in female prisoners: pragmatic skills are essential - Morken, Frøydis; Helland, Wenche Andersen; Evanger, Elisabeth; Vårvik, Aslaug; Jones, Lise Øen (Frontiers in Psychology, 2023)
There are strong indications of an elevated incidence of both language problems and problems with mental health among prisoners. We also know that women in prison are a particularly vulnerable group who often face conditions that foremost accommodate the needs of men. In order to adapt prison conditions to women's needs and give better help, we need more information about their characteristics. In this study, we wanted to explore associations between oral language problems and mental health (depression and anxiety) in women in prison. Participants were 58 women, recruited from high and low security women's and mixed prisons. They completed a questionnaire covering demographic variables and several self-report measures. In the present study, the language measures were a Language Composite score (comprising articulation, impressive and expressive language, and pragmatics) and the LaTrobe Communication Questionnaire (LCQ), measuring pragmatic skills specifically. Hopkins Symptom Checklist-10 (HSCL) was used as a measure of psychological distress. First, we assessed correlations between the language measures and mental health. Second, we performed group comparisons with groups defined as over or under cut-off on the Language Composite, LCQ total, and HSCL total scores. Results supported a clear connection between overall language and overall mental health. Pragmatic skills were the main driver of this effect. There was no difference in mental health between those scoring above and below cut-off for general language problems but the group with possible pragmatic impairment showed poorer mental health than those without. Conversely, there was no difference in general language skills between the groups scoring within and outside the range of psychological distress, but the first group evaluated their pragmatic This is a provisional file, not the final typeset article skills as significantly poorer than the latter. We conclude that pragmatics seem to be core to the association between oral language skills and mental health among female prisoners. This should have implications for language services in prisons, as attending to these issues could positively affect prognosis and outcome.